2019
DOI: 10.1101/655431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biogeographical patterns in soil bacterial communities across the Arctic region

Abstract: The considerable microbial diversity of soils, their variety and key role in biogeochemical cycling has led to growing interest in their global distribution and the impact that environmental change might have at the regional level. In the broadest study of Arctic soil bacterial communities to date, we used high-throughput DNA sequencing to investigate the bacterial diversity from 200 independent Arctic soil samples from 43 sites. We quantified the impact of spatial and environmental factors on bacterial commun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 67 publications
6
13
0
Order By: Relevance
“…This suggests that soil microclimate, which better expresses the temperature and moisture conditions affecting below‐ground and ground‐dwelling organisms and which can be strongly decoupled from air temperature in space and time (see also Bramer et al., 2018; Graae et al., 2012; Scherrer & Körner, 2011; Suggitt et al., 2011), likely also better explains the distributions of soil microorganisms. Furthermore, other edaphic factors (particularly soil pH) and biotic interactions are known to be major drivers for the diversity and community structure of soil fungi and bacteria (Bahram et al., 2018; Bates et al., 2013; Fierer et al., 2009; Li et al., 2018; Malard, Anwar, Jacobsen, & Pearce, 2019; Yashiro et al., 2016), and also but to a lesser extent for the diversity of protists (Seppey et al., 2020). Thus, they can also be expected to strongly contribute to explain the distribution of individual soil microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that soil microclimate, which better expresses the temperature and moisture conditions affecting below‐ground and ground‐dwelling organisms and which can be strongly decoupled from air temperature in space and time (see also Bramer et al., 2018; Graae et al., 2012; Scherrer & Körner, 2011; Suggitt et al., 2011), likely also better explains the distributions of soil microorganisms. Furthermore, other edaphic factors (particularly soil pH) and biotic interactions are known to be major drivers for the diversity and community structure of soil fungi and bacteria (Bahram et al., 2018; Bates et al., 2013; Fierer et al., 2009; Li et al., 2018; Malard, Anwar, Jacobsen, & Pearce, 2019; Yashiro et al., 2016), and also but to a lesser extent for the diversity of protists (Seppey et al., 2020). Thus, they can also be expected to strongly contribute to explain the distribution of individual soil microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Biogeographical patterns have been identified in the phyllosphere of other tree species [ 15 , 80 ]. However, few studies have examined the biogeographical patterns of different microbial populations in the phyllosphere (e.g., rare versus abundant and core versus non-core taxa) as in other environments [ 16 , 45 , 81 ]. Our results revealed that biogeographical patterns were strongest in non-core taxa, exhibiting a non-random distribution across space and environmental gradients that contrasted with the cosmopolitan distribution of the relatively dominant core microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Total organic carbon, pH and conductivity were identified as the key drivers of bacterial diversity across the Arctic landscape and are also commonly identified in studies across the globe (8,(34)(35)(36)(37)(38). While pH was previously identified as the primary driver of bacterial diversity in Arctic soils across the whole Arctic region (19); here, at the landscape scale, TOC was identified as the primary factor influencing bacterial community structure and was tightly linked with soil moisture. Generally, soil organic carbon content increases with increasing precipitation and decreasing temperature (39).…”
Section: Key Environmental Factors Influencing Bacterial Communitiesmentioning
confidence: 73%
“…S1] across an Arctic landscape [Fig 1]. Indeed, while the role of environmental parameters such as pH (17,18), total organic content (TOC) (19), moisture content (20) and C:N ratio (21) on community composition in the Arctic has been demonstrated, much less is known about the influence of spatial parameters (19). However, determining the influence of environmental factors on communities remains an essential step to avoid overestimating the role of the spatial scale.…”
Section: Introductionmentioning
confidence: 99%